Capital Requirements for Securities Firms. - Dimson, Elroy; Marsh, Paul (Journal of Finance, 1995)
Regulatory authorities set capital requirements to cover the position risk of securities firms and to protect against losses arising from fluctuations in the value of their holdings. The requirements may be set using the comprehensive approach required by the U.S. Securities and Exchange Commission, the building-block approach required by the European Community, or the portfolio approach required by the United Kingdom. We compare these three alternatives using a large sample of U.K. equity trading books. The portfolio approach systematically specifies larger requirements for riskier books, and vice versa. It is more efficient than the building-block approach, and far more efficient than the comprehensive approach.